PELATIHAN PEMBUATAN NUGGET AYAM DI OPHIR NAGARI KOTO BARU KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Yayuk Sri Utami (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Chicken nuggets are processed foods for chicken meat that have a high taste and favor the community. This activity aims: 1. to increase knowledge of how to make nuggets at home for the people of Jurong Ophir Nagari Koto Baru, 2. to improve the understanding and skills of the people of Jurong Ophir Nagari Koto Baru on how to make nuggets at home, and 3. to increase the income of chicken farmers in Jurong. Ophir Nagari Koto Baru. Meanwhile, the target of this activity is women and the people of Jurong Ophir. The methods used in this activity are counseling, demonstration, mentoring, and evaluation. The counseling provided is in the form of information related to chicken in nutritional content, shelf life, types of chicken derivative products, and the right technology in making the chicken derivative products. At the same time, the demonstration was carried out by the direct practice of making chicken nuggets. Each activity carried out mentoring and evaluation to determine the achievement of targets. The implementation of the activity went well, and even the participants were enthusiastic about participating in the training on making chicken nuggets. From this activity, there was an increase in the knowledge and skills of participants in making chicken nuggets. This activity has been able to help the people of Jurong Ophir Nagari Koto Baru to increase additional income for the community. From this activity, it can be concluded that the implementation of the activity has been successful and has received a good response. It is hoped that this training can increase the motivation of the participants to start the chicken nugget business to improve the community's economy. For the sustainability of this activity, assistance is needed so that the efforts carried out by mothers can develop and be sustainable.